Enhancing the Solubility and Dissolution Rate of Tenoxicam through Co-Amorphous Formation with Meglumine by a Solvent Dropped Grinding Method - Fitriani, Lili; Arif, Zhafira; Hasanah, Uswatul; Zaini, Erizal (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Tenoxicam is a non-steroidal anti-inflammatory drug (NSAID), one of the oxicam group. It is categorized as Biopharmaceutical Classification System class II, as its low solubility and high permeability. The aims of this research were to enhance the solubility and dissolution rate of tenoxicam by its modification into a co-amorphous phase with meglumine at a molar 1:1 ratio. The co amorphous form of tenoxicam-meglumine was prepared by a solvent drop grinding method, and characterized by thermal analysis using differential scanning calorimetry (DSC), solid phase by powder X-ray diffraction (PXRD), identification of functional group by Fourier-transform infrared (FT-IR) spectroscopy, and morphology by polarized light microscopy (PLM) and scanning electron microscopy (SEM). The solubility test was conducted in water, whereas the dissolution test was performed in 0.1 N HCl solution and water. The DSC thermogram demonstrated a decrease in the endothermic peak of the co-amorphous tenoxicam-meglumine. The PXRD diffractogram revealed a reduction in the peak intensity of the X-ray diffraction, which formed a halo pattern. The FT-IR spectroscopy analysis indicated the formation of the co-amorphous system. The co-amorphous of tenoxicam-meglumine solubility’s increased by 42.71-fold as compared to intact tenoxicam. The co-amorphous tenoxicam meglumine exhibited a dissolution rate of 92.71% and 100% in 0.1 N HCl and distilled water, respectively, after 60 minutes, and resulting in separate increases in dissolution efficiency by 3.05 and 9.12-times in 0.1 N HCl and distilled water. In summary, the formation of the co-amorphous phase of tenoxicam and meglumine successfully enhanced the solubility and dissolution of tenoxicam.